Üniversite Öğrencilerinin Sağlıklı Yaşam Biçimi Davranışlarının ve Fiziksel Aktivite Düzeylerinin Araştırılması - Erdoğan, Ramazan; Tel, Mikail; Tan, Çetin; Tan, Suriye (Gaziantep University, 2022)
Amaç: Bu araştırma üniversite öğrencilerinin sağlıklı yaşam biçimi davranışları ve fiziksel aktivite düzeylerini belirlemek amacıyla yapılmıştır. Yöntem: Araştırma grubunu Bitlis Eren Üniversitesinde öğrenim gören 337 (157 Kadın, 180 Erkek) gönüllü öğrenci oluşturmuştur. Veri toplama aracı olarak öğrencilerin demografik bilgilerini ve sağlıklı yaşam biçimlerinin sorgulandığı online bir anket formu uygulanmıştır. Verilerin analizinde SPSS paket programından faydalanılmıştır. Anlamlılık düzeyi p

Aim: This research was conducted to determine the healthy lifestyle behaviors and physical activity levels of university students. Materials and Methods: The research group consisted of 337 (157 Female, 180 Male) volunteer students studying at Bitlis Eren University. As a data collection tool, an online questionnaire was applied, in which students' demographic information and healthy lifestyles were questioned. SPSS package program was used in the analysis of the data. Significance level was accepted as p
Investigation of University Students' Healthy Lifestyle Behaviors and Physical Activity Levels
Keywords: Sports Medicine; Spor Hekimliği